CONTRACEPTIVE ADAPTATION AMONG LACTATING MOTHERS: A CASE STUDY OF RAJA KA PURWA SLUM IN KANPUR - Sharma, Abhilasha; Ahmed, Dr. Shaizy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In today's expanding globe, family planning is becoming increasingly popular among young married couples living in urban or rural areas. The sustainable use of modern contraceptive methods is considered the most efficient means to control family sizes. It helps young married couples plan their family sizes by facilitating the efficient use of birth control. Lactating mothers are at greater risk of getting an unexpected and unwanted pregnancy because of inadequate age differences between the children. It may further increase the dire need to embrace family planning among women. Contemporary birth control methods give opportunities to young married couples to regulate their fertility, which further helps them plan their family sizes. The authors used a qualitative research approach to explore the extent and limitations of contraceptive usage among lactating mothers. Purposive sampling was employed to choose 50 lactating mothers in the Raja Ka Purwa slum in Kanpur, India. Data is gathered through Focused Group Discussion and interpreted through Thematic Analysis. The findings reveal that lactating mothers in the Raja Ka Purwa slum do not have any desire to regulate their family sizes. These women often avoid using contemporary birth control techniques due to ignorance, several health concerns, misbeliefs, and family discouragement. The study concluded that there is an urgent need to implement grassroots initiatives with the help of community healthcare workers, including AWWs, ASHAs, and ANMs, to promote reproductive health literacy to motivate women to have better autonomy in their reproductive health, particularly those living in slum areas, to utilize family planning.